2014
DOI: 10.1039/c4fd00010b
|View full text |Cite
|
Sign up to set email alerts
|

Cold condensation of dust in the ISM

Abstract: The condensation of complex silicates with pyroxene and olivine composition at conditions prevailing in molecular clouds has been experimentally studied. For this purpose, molecular species comprising refractory elements were forced to accrete on cold substrates representing the cold surfaces of surviving dust grains in the interstellar medium. The efficient formation of amorphous and homogeneous magnesium iron silicates at temperatures of about 12 K has been monitored by IR spectroscopy. The gaseous precursor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 33 publications
3
35
0
Order By: Relevance
“…This study is therefore not able to solve this long-standing conundrum. Although recent experiments Rouillé et al 2014) show that it may be possible to form silicates under ISM conditions. However, it seems that the modelling of silicate sputtering together with hydrodynamical simulations of shock dynamics are absolutely critical to advance our understanding and will possibly give lower silicate sputtering resulting in a longer lifetime t SNR,s 6 × 10 8 yr.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study is therefore not able to solve this long-standing conundrum. Although recent experiments Rouillé et al 2014) show that it may be possible to form silicates under ISM conditions. However, it seems that the modelling of silicate sputtering together with hydrodynamical simulations of shock dynamics are absolutely critical to advance our understanding and will possibly give lower silicate sputtering resulting in a longer lifetime t SNR,s 6 × 10 8 yr.…”
Section: Discussionmentioning
confidence: 99%
“…However, as pointed out by Jones & Nuth (2011), silicate re-formation under the low density and temperature conditions of the ISM seems to be a rather problematic scenario. However, SiO and silicate grain formation at low temperatures (T 15 K) has been observed in the laboratory using idealised neon matrix and helium droplet isolation techniques Rouillé et al 2014). The oligomerisation of SiO molecules is barrierless and therefore could be an efficient mechanism for silicate formation in the low-temperature ISM .…”
Section: Consequences Of the Uncertaintiesmentioning
confidence: 99%
“…Dwek et al 2007;Michałowski et al 2010aMichałowski et al , 2010bHirashita & Kuo 2011;Valiante et al 2011;Kuo & Hirashita 2012;Mancini et al 2015;Michałowski 2015). Recent experiments by Rouillé et al (2014) showed that accretion actually occurs in cold environments.…”
Section: Constraint On the Parametersmentioning
confidence: 99%
“…b á ñ a 3 derived from Equation (9) for the enhancement factor D(a) for silicate grains in the CNM. recent experiments in Jena thatdemonstrate that adsorbed species can form chemical bonds characteristic ofsilica and silicates at substrate temperatures of 10K without an activation barrier Rouillé et al 2014).…”
Section: Sticking Coefficientmentioning
confidence: 99%